2021
DOI: 10.3390/jpm11090861
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determination of mirRNA-126 rs4636297, Phosphoinositide-3-Kinase Regulatory Subunit 1-Gene Variability rs7713645, rs706713 (Tyr73Tyr), rs3730089 (Met326Ile) and Their Association with Susceptibility to T2D

Abstract: Type 2 diabetes is a metabolic disease characterized by elevated blood sugar. It has serious complications and socioeconomic impact. The MicroRNAs are short single-stranded and non-coding RNA molecules. They regulate gene expression at the post-transcriptional levels. They are important for many physiological processes including metabolism, growth, and others. The phosphoinositide 3-kinase (PI3K) is important for insulin signaling and glucose uptake. The genome wide association studies have identified the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…T2DM is the result of the combined effects of genetic background, gender, aging, lifestyle, obesity and other factors. 6 , 7 , 26 Age and gender differences in the risk, onset, and progress of T2DM were found in previous studies. 27 , 28 When stratified by gender and age, rs3825199, rs11107116, and rs10492321 were conferred to an increased T2DM risk among males, and among the subjects aged ≤60 years ( Suppl_Table 3 ).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…T2DM is the result of the combined effects of genetic background, gender, aging, lifestyle, obesity and other factors. 6 , 7 , 26 Age and gender differences in the risk, onset, and progress of T2DM were found in previous studies. 27 , 28 When stratified by gender and age, rs3825199, rs11107116, and rs10492321 were conferred to an increased T2DM risk among males, and among the subjects aged ≤60 years ( Suppl_Table 3 ).…”
Section: Discussionsupporting
confidence: 52%
“… 5 In addition, genetic factors are strongly contributed to the etiology and manifestation of T2DM. 6 , 7 To date, a variety of risk loci affecting T2DM susceptibility have been recognized, 8–10 but numerous loci remain to be detected.…”
Section: Introductionmentioning
confidence: 99%
“…They have been found to have an effect on glucose metabolism. For example, a recent study showed that miR-126 single nucleotide polymorphism was associated with T2DM[ 101 ]. MiRNAs may be a target therapeutic strategy in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, β-thalassemia prenatally was diagnosed by successfully using ARMS-PCR system in China and in Iran (Fu et al, and Moghadam et al), respectively [ 26 , 27 ]; Chiu et al, utilized ARMS-PCR to detect the wild as well as mutant mitochondrial tDNA heteroplasmies [ 28 ], whereas ARMS-PCR was applied to the antenatal diagnosis of cystic fibrosis [ 29 ]. Rashid Mir et al, applied ARMS-PCR for studying genotyping in coronary artery disease, breast cancer and also utilized ARMS-PCR for microRNA genotyping [ 30 , 31 , 32 , 33 ]. Recently, Singh et al [ 34 ] utilized ARMS PCR for prenatal diagnosis for SCD.…”
Section: Discussionmentioning
confidence: 99%